Lifespan and associated factors of peripheral intravenous Cannula among infants admitted in public hospitals of Mekelle City, Tigray, Ethiopia, 2016 - Eskedar Birhane; Kalayou Kidanu; Mekuria Kassa; Dawit Gerezgiher; Lidia Tsegay; Brhanu Weldu; Genet Kidane; Hadgu Gerensea (BMC, 2017)
Abstract Background Peripheral Intravenous cannula (IV) is the most common vascular access device used to administer medications with the exception of medication or fluid with high or low PH or hyperosmolarity which may cause severe damage to small veins. The insertion of a peripheral intravenous cannula in newborn infants can be difficult. Appropriate veins with sufficient capacity to insert a cannula become less available throughout the hospital stay. Once a peripheral intravenous cannula is inserted, it is desirable that its patency can be maintained as long as possible. This study was aimed to assess the lifespan and associated factors of peripheral intravenous cannula among infants admitted in public hospitals of Mekelle city, Tigray, Ethiopia, 2016. Methods The method used was a prospective cohort study. 178 study subjects were recruited using systematic random sampling technique. The data was collected by structured questionairre and observational checklist. Results More than half of infants (94) had a short cannula lifespan (below 30 h). Multivariable logistic regression analysis showed that Pediatric intensive care unit (PICU) [AOR = 6.93; 95% CI (1.56,30.71)], clinical experience (3-5 years) [AOR = 0.168; 95% CI (0.060-0.469)], insertion site (arm) [AOR = 0.126;95% CI (0.046-0.349)], reason for removal (dislodgement and complication) [AOR = 8.15; 95% CI (2.49,26.63) [AOR = 10.48;95% CI (3.08,35.65)], medication [AOR = 0.17;95% CI (0.37,0.784)], corticosteroids [0.164; 95% CI (0.034,0.793)] and blood transfusion [AOR = 0.12; 95% CI (0.028-0.509)] were the statistically significant variables associated with the lifespan of a peripheral intravenous cannula. Conclusions Untimely removal of peripheral intravenous cannulas was higher in infants and demographic. Cannulation and health care factors had significant effects on the lifespan of a peripheral intravenous cannula.